Lost in the customhouse : authorship in the American renaissance - Loving, Jerome, 1941- (University of Iowa Press, 1993)
In this vigorous challenge to dominant literary criticism, Jerome Loving extends the traditional period of American literary rebirth to the end of the 19th century and argues for the intrinsic value of literature in the face of new historicist and deconstructionist readings. Bucking the trend for revisionist interpretations, Loving discusses the major work of the 19th century's canonized writers as restorative adventures with the self and society. From Irving, Hawthorne, Melville, Poe, Thoreau, and Emerson to Whitman, Twain, Dickinson, James, Chopin, and Dreiser, Loving finds the American liter.